Functional outcome of Schatzker type V and VI tibial plateau fractures managed by open reduction and internal fixation using dual plates - Haider, M. Ali; Hossain, M. Iqbal; Ahmed, Wakil; Tuhin, Jabed Jahangir; Paul, Ratan Kumar; Hasan, M. Rashed; Hasibuzzaman, M. (International Journal of Research in Orthopaedics, 2024)
Background: High-energy bicondylar tibial plateau fractures (Schatzker type V and VI) occur as a result of road traffic accidents, falls from height, and sports injuries, and mostly affect the younger age group in productive life years. This study aimed to evaluate the functional outcome of high-energy tibial plateau fractures (Schatzker type V and VI) treated by dual plating through anterolateral and posteromedial incisions. Methods: This was a hospital-based clinical trial study conducted in the department of orthopaedics and traumatology, Chittagong medical college hospital, Chattogram, Bangladesh, from January 2018 to December 2019. Our study included 50 adult patients of both genders with high-energy tibial plateau fractures through a consecutive sampling technique. The knee function of the patients was evaluated according to the Oxford knee scoring system. Results: Out of 50 cases, 38 cases (76%) were male and 12 cases (24%) were female with a mean±SD age was 43.95±10.89 years. All the cases (100%) were due to RTA, 70% had Schatzker type VI and 30% had type V injury. Mean±SD time interval from injury to fixation was 11.05±3.20. The average duration of operation in minutes was 107.0 (±12.07). At the final follow-up, 41 (82%) and 05 (10%) patients had excellent and good outcomes respectively. Conclusions: Open reduction and internal fixation in high-energy tibial plateau fractures using dual plates through two incisions can provide excellent to good functional results and minimal soft tissue complications in appropriately selected cases.